Um estudo sobre o Sistema Tributário e a desigualdade de renda no Estado do Ceará - Homsi, Tereza Cristina Apoliano (2017)
This dissertation makes a study about the repercussion of the tax system, represented by the Imposto sobre Operações relativas a Circulação de Mercadorias e sobre Prestação de Serviços de Transporte Interestadual e Intermunicipal e de Comunicação - ICMS and Imposto de Renda da Pessoa Física - IRPF, on inequality income in the state of Ceará. The objective of the study is to verify if the ICMS is regressive, burdening the poorest income classes more, and if the IRPF compensates the regressivity of the ICMS. Information extracted from the microdata of the Family Budget Survey (POF) 2008/2009, on the consumption of the households of Ceará, in the areas of food-Free, food-Basic Basket, food-General, food outside the home, alcoholic beverages, transportation, energy, tobacco, jewelry, medicines, and garments. The econometric method of simple regression by the Ordinary Least Squares was used to estimate the Engel curves in order to determine the income elasticities of the demand of the selected products in relation to the respective expenditures. The results show that the incidence of ICMS is regressive, and that the progressive nature of the IRPF compensates for it. It is concluded that the poorest classes are the ones that are the most taxed, being one of the factors responsible for the inequality of income distribution in the State of Ceará.